ELEMENTARY STUDENTS MATHEMATICAL PROBLEM-SOLVING VIEWED FROM INTERPERSONAL INTELLIGENCE - Permataari, Desty Ratna; Soegiyanto, Heribertus; Usodo, Budi (Journal on Mathematics Education)
Problem-solving ability is one of the fundamental skills that must be mastered by students because problem-solving skills will help to solve problems in other subjects as well as everyday life. Therefore, the problem-solving ability is a common goal of learning mathematics. Success in mathematical problems solving is influenced by student abilities and skills in creating social relations. Student abilities and skills in creating social relations and to work effectively with others called interpersonal intelligence. This research aims to describe mathematical problem solving of elementary students used the descriptive qualitative method which data was collected through questionnaire, test, and interview. Results showed that students with high interpersonal intelligence could master four indicators of problem-solving, namely understand the problem, devise a plan, carry out the idea, and lock back. Students with average interpersonal intelligence can master understands the problem and design a plan indicator, but sometimes they cant carry out the plan correctly. Students with low interpersonal intelligence just understanding the problem, but they cant devise the plan well.